Optic Disc and Cup Segmentation Methods for Glaucoma Detection Using Retinal Fundus Images - Dr. Jayanthi P. Mr. Shivaa R, Mr. Sownthear D, Mr. Soundar T (International Journal of Advanced Science and Technology, 2020)
The leading cause of blindness in our country is due to Glaucoma. Glaucoma contributes to 6.7 million causing them blind. The Excess size of optic cup leads to glaucoma since the optic cup occupies the area of the optic disc. The glaucoma can be diagnosed by determining the Cup to Disc (CDR) ratio which enables us to determine the enlargement of optic cup. The ratio can be obtained by segmenting the OC and OD from the retinal fundus images. The architecture was used for segmentation purpose is Convolutional Neural Network. The dataset was obtained from the DRIONS-DB and RIM-ONE databases that are publicly available. The proposed technique will find the best algorithm that is used for Glaucoma detection.